Theoretical study of the structural stability, electronic and magnetic properties of XVSb (X = Fe, Ni, and Co) half-Heusler compounds - Mokhtari, M.; Dahmane, F.; Benabdellah, G.; Zekri, L.; Benalia, S; Zekri, N. (Condensed Matter Physics, 2018)
The structural, electronic and magnetic properties of half-Heusler compounds XVSb (X = Fe, Co and Ni) are investigated by using the density functional theory with generalized gradient approximation (GGA), and Tran-Blaha
modified Becke-Johnson (TB-mBJ) exchange potential approximation. It is found that the half-metallic gaps are
generally reasonably widened by mBJ as compared to the GGA approximation. The magnetic proprieties of XVSb
(X = Fe, Co and Ni) are well defined within mBJ with an exact integer value of magnetic moment. The band gaps
given by TB-mBJ are in good agreement with the available theoretical data. The FeVSb exhibits a semiconductor
nature. The CoVSb and NiVSb present half-metallic behaviour with total magnetic moment of 1µB and 2µB in
good agreement with Slater-Pauling rule. These alloys seem to be a potential candidate of spintronic devices. Структурнi, електроннi та магнiтнi властивостi напiв-Гойслерiвських сполук XVSb (X = Fe, Co i Ni) дослiджено з використанням теорiї функцiоналу густини разом з узагальненим градiєнтним наближенням (GGA)
та Тран-Блаха модифiкованим Беке-Джонсон (TB-mBJ) наближенням обмiнного потенцiалу. Встановлено,
що напiвметалiчнi щiлини загалом достатньо розширенi за рахунок mBJ у порiвняннi з наближенням
GGA. Магнiтнi властивостi XVSb (X = Fe, Co i Ni) добре визначенi в межах mBJ при точному цiлому значеннi магнiтного моменту. Ширина заборонених зон, отримана з TB-mBJ, добре узгоджується з наявними
теоретичними даними. FeVSb проявляє напiвпровiдниковий характер. CoVSb i NiVSb показують напiвметалiчну поведiнку при сумарному магнiтному моментi 1µB i 2µB, що добре узгоджується з правилом
Слейтера-Паулiнга. Видається, що цi сплави є потенцiйними кандидатами для використання у спiнтронних пристроях.